Does Radical Lymphadenectomy Improve Survival in Esophageal and Gastroesophageal Junction Cancer? - Adhikari , Mahesh Mani; Thakur, Binay; Shun, Zhenqing; Khatiwada, Sagar; Bhattarai, Sachee; Tiwari, Manoj (Nepalese Journal of Cancer, 2024)
Background: Esophageal carcinoma is one of the deadliest cancer in gastrointestinal system with 5-years survival of only 24%. Lymphnode metastasis has been associated with worse outcome. But the extent of lymphnode dissection has been a debate among surgeons worldwide. This study aimed to compare the overall survival of patients undergoing radical and non-radical lymphadenectomy in a tertiary referral cancer hospital in Nepal. Methodology: This study included 634 patients of esophageal and gastroesophageal junction cancer who underwent surgical resection at our institution over a period of 2001- 2019. The patients were divided into 2 groups; radical lymphadenectomy (RLN) and non-radical lymphadenectomy (NRLN) groups. RLN group underwent two-field or three field lymphadenectomy for esophageal cancer and D2 or D2 + lower mediastinal lymphadenectomy for GEJ cancer. NRLN group underwent nodal sampling or D1 dissection. Results: RLN was performed in 85.9%. NRLN was done in 14.1%. Surgery alone was performed in 47.1% and multimodality approach in 52.9% cases. Median survival for RLN and NRLN groups was 34 and 15 months, respectively (p < .001). Conclusion: Improved median survival has been observed after radical lymphadenectomy for esophageal and GEJ cancer.